Description of the immatures of workers of the ant camponotus vittatus (Hymenoptera: Formicidae) - Solis, Daniel Russ [UNESP]; Fox, Eduardo Gonçalves Paterson [UNESP]; Rossi, Mônica Lanzoni; Moretti, Thiago De Carvalho [UNESP]; Bueno, Odair Correa [UNESP] (De Gruyter, 2010)
Camponotus vittatus Forel is a poorly studied Neotropical ant, which is very common in Brazil. Larval descriptions are useful to systematics, as larval characters aid with genus-level differentiation, and ant larvae lie at the basis of ant social organization. This study presents the first description of the immatures of C. vittatus with the aid of light and scanning electron microscopy. There are three instars based on the frequency distribution of larval head widths. The larvae had some characteristics typical of Camponotus, specifically, a 'pogonomyrmecoid' body shape, 10 pairs of spiracles, antennae with 3 sensilla, mature larvae with pronounced labial pseudopalps, and conspicuous 'chiloscleres' on the labrum. Unique characteristics found would include the greatest diversity of body hair types recorded in an ant larva and 'camponotoid' mandibles with 6 medial denticles over the blade. The number of antennal sensilla proved variable.
Keywords: Tanaemyrmex